Analisis Penggunaan Akuntansi Syariah Terhadap Pembiayaan Syariah Berdasarkan PSAK No. 102 Pada PT Bank Syariah Indonesia, Tbk - Fahri Widyatmoko (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2023)
The purpose of this study is to determine the usability of the implementation of murabahah financial accounting in PT Bank Syariah Indonesia, Tbk Cimahi Branch Accounting Standards No. 102 on Murabahah Accounting. This type of research is a qualitative descriptive research that describes and explains the application of the murabahah system in Islamic banking. The data sources used by the author are direct data sources (primary data) and indirect data sources (secondary data). In this study, the data collection technique was field research, ie. field data collection through documentation and interviews. In this work, the author uses the method of comparative analysis. Comparative analysis method is a problem solving method or procedure that is studied by comparing accounting applied to Islamic mortgage financing in PT Bank Syariah Indonesia, Tbk Cimahi Branch with PSAK 102 based murabahah contract.